Les travaux préparatoires et l'interprétation du Code civil du Québec - Normand, Sylvio (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
Long rejected as a means of interpretation of the Civil Code, the travaux préparatoires have recently been rehabilitated ; henceforth nothing will be opposed to the consultation of the Codiflers' Reports or of the Report on the Québec Civil Code by the Civil Code Revision Office. Parliamentary debates, however, are not yet to be quoted. But, taking into account the restrictive interpretation recently given to Reader's Digest case, in addition to what the preamble of the Act to establish a new Civil Codeand to reform family law expresses, the author considers it justified to come back to the Journal des Débats to light the finality of certain dispositions ulterior to Office Report.